Characteristics of regional odontodysplasia: A case report - doi 10.4025/actascihealthsci.v34i2.13380 - Lima, Saulo André de Andrade; Oliveira, Amilcar Viana de; Lima, Luciana Silveira Gonçalves; Paranhos, Luiz Renato; Jóias, Renata Pilli; Siqueira, Danilo Furquim (Acta Scientiarum. Health Sciences, 2012)
Regional odontodysplasia is an uncommon, nonhereditary developmental dental disorder of unknown etiology, which should be early detected. This paper compares a regional odontodysplasia case with the clinical and radiographic characteristics reported in the literature, showing a 1y6m follow up and the limitations of performing a multidisciplinary esthetic and functional treatment.